Ferrugem-asiática da soja: interações entre cultivares e volumes de calda no controle da doença e sensibilidade de Phakopsora pachyrhizi a fungicidas - Moura, Bianca de (2018)
Since the detection of Asian soybean rust, caused by Phakopsora pachyrhizi, in Brazil, fungicide application on plants aerial parts has been the most used strategy for disease management and control. However, a reduction in the effectiveness of chemical control has been observed in recent seasons. Therefore, this work aimed to evaluate the control of the Asian soybean rust as a function of fungicide spray volume and nozzles, as well as the sensitivity of P. pachyrhizi to the most used fungicides. In an experiment conducted in the experimental field of the FAMV / UPF in the 2015 / 2016 and 2016 / 2017 seasons, in a completely randomized design with six replicates, six soybean cultivars (three with indeterminate growth habit and three with determinate habit) were submitted to the following treatments: fungicide applications with a spray volume of 50 L / ha with hollow cone nozzles, applications with a fungicide spray volume of 120 L / ha with flat fan nozzles and plants without application (Check). The rust severity was evaluated until the end of the physiological maturation to quantify the evolution of the disease and obtain the area under the disease progress curve (AUDPC). Also, for the three indeterminate growth cultivars during the 2015 / 2016 season, a fluorescent marker was added to the third fungicide application, to determine the deposition and percentage of foliolar coverage on the upper, middle and bottom portions of the plant canopy. In the 2015 / 2016 season, the application with 120 L / ha spray volume provides greater coverage on the upper and middle canopies, exceeding the application with a volume of 50 L / ha by 18.6% disease control. However, there are no differences in the spray deposit levels on the three portions of the plant canopy. In the 2016 / 2017 season, a significant difference is observed in the grain yield for two of the six cultivars submitted to fungicide applications with different spray volumes. In another experiment, conducted in the Laboratory of Phytopathology at the FAMV / UPF, the fungitoxicity of three fungicide mixtures was evaluated against 14 P. pachyrhizi isolates from soybean producing Brazilian regions by determining the inhibitory concentration in vitro (IC50). For the Passo Fundo - RS isolate, the IC50 of each active ingredient present in the mixtures was determined. In a completely randomized design with four replicates, fungicides were incorporated in different concentrations in Petri dishes containing the agar-water substrate for further quantification of viable uredospores. The fungicide azoxystrobin + benzovindiflupyr is highly fungitoxic for nine of the 14 tested isolates. Both triple mixtures, bixafem + prothioconazole + trifloxystrobin and epoxiconazole + fluxapiroxade + pyraclostrobin are highly fungitoxic to 12 of the 14 isolates. The fungicides azoxystrobin, epoxiconazole, pyraclostrobin and trifloxystrobin and the mixtures pyraclostrobin + fluxapiroxade and prothioconazole + trifloxystrobin show a reduction in the IC50 for the Passo Fundo isolate, compared to previous studies. There are alterations, both in the sensitivity between isolates to the active ingredients tested, and in relation to IC50 values obtained with previous studies.